Sustainable Commerce Practices: Green Marketing and Ethical Consumerism - K. Sunitha (AG Volumes, 2024)
Consumers are moving towards eco-friendly goods as a result of growing environmental consciousness worldwide, which makes green marketing a crucial component of modern corporate strategy. This research article reviews the various literature’s study of Green Marketing and Ethical Consumerism. The chapter concludes that green marketing has become essential for businesses, offering environmental and economic benefits while enhancing public perception. To appeal to ethical customers and government agencies, businesses are incorporating sustainable practices including waste minimisation, energy efficiency, and environmentally friendly products. Digital marketing plays a key role in promoting green products, as the interest among people using green products increased post-COVID-19. Ethical consumerism, driven by transparency and accountability, influences purchasing behaviour. Third-party certifications strengthen consumer trust, while green strategies encourage sustainable consumption. Businesses must align with ethical values to foster brand loyalty. Addressing global environmental challenges, green marketing remains crucial in shaping responsible consumer behavior and long-term business success.